Evaluating the low back biomechanics of three different office workstations: Seated, standing, and perching. (September 2016) - Le, Peter; Marras, William S.
Abstract: The objective of this study was to evaluate how different workstations may influence physical behavior in office work through motion and how that may affect spinal loads and discomfort. Twenty subjects performed a typing task in three different workstations (seated, standing, and perching) for one hour each. Measures of postural transitions, spinal loads, discomfort, and task performance were assessed in order to understand the effects of workstation interaction over time. Results indicated that standing had the most amount of motion (6–8 shifts/min), followed by perching (3–7 shifts/min), and then seating (<1 shift/min). Standing had the highest reports of discomfort and seating the least. However, spinal loads were highest in A/P shear during standing (190N posterior shear, 407N anterior shear) compared to perching (65N posterior shear, 288N anterior shear) and seating (106N posterior shear, 287 anterior shear). These loads are below the risk threshold for shear, but may still elicit a cumulative response. Perching may induce motion through supported mobility in the perching stool, whereas standing motion may be due to postural discomfort. Office workstation designs incorporating supported movement may represent a reasonable trade-off in the costs-benefits between seating and standing. Highlights: Perching was associated with lower spinal loads compared to standing. Supported movement resulted in lower discomfort relative to prolonged standing. Heart rate variability may provide an objective understanding of discomfort.